SPEECH FORMATION OF CHILDREN WITH AUTISM USING ABA THERAPY - Аутаева, А.Н.; Бекмурат, Айдос; Меирбекова, А. (Pedagogy and Psychology, 2023)
The number of children with autism spectrum disorders is growing every day. However, recently applied behavioral analysis (ABA therapy) has been widely used to correct this disorder. A number of early intervention models based on ABA principles are a curriculum for teaching children with autism spectrum disorders. One of them is a model of Verbal Behavior analysis of B. F. Skinner, developing speech in an autistic child. The VB approach is based on ABA research. And increases the child's ability to learn a functional language. This method allows children with autism and related disorders to form and develop spoken language, focusing not only on how they speak, but also on the purpose for which the child uses speech. This article attempts a theoretical analysis and description of the use of Verbal behavior based on ABA in the development of speech in a child with autism.